Peritonsillar Infiltration with Tramadol and Bupivacaine to Relief Post-Tonsillectomy Pain in Children - Khudhair, Esam Shyaa; Abutiheen, Ali A. Kadhim; Dakhal, Hadeer Jabbar; Yassin, Ammar Gany (Karbala Journal of Medicine, 2021)
Background: Tonsillectomy is one of the most frequently performed surgical interventions in children. Pain control for pediatric’ patients undergoing tonsillectomy remains problematic. Objectives: To investigate the effects of peritonsillar infiltration of tramadol and bupivacaine in reducing post-tonsillectomy pain in children. Patients and methods: A Quasi-interventional study, 150 children aged 5-15 years, who were scheduled for elective tonsillectomy or adenotonsillectomy at the ENT department. Patients were randomly allocated into three groups with 50 patients in each. Group A received peritonsillar infiltration of tramadol, group B received peritonsillar infiltration of 5ml of 2 % Bupivacaine. While equal quantities of isotonic saline were used for infiltration in the control group (C). In all groups, peritonsillar infiltration was carried out after tonsillectomy but before to tracheal extubation. Postoperative pain was evaluated by a visual analog scale (VAS) and compared for the three groups. Results No significant difference between the groups in regards to age, gender, weight, type of surgery, and duration of the operation. The tramadol group shows a significantly lower pain score in the early postoperative hours in comparison to the bupivacaine and control groups. Further, the bupivacaine group shows a significantly lower pain score in comparison to the control group within the first hour postoperatively. No significant difference was found between the groups regarding nausea and vomiting side effects. Conclusions: Peritonsillar infiltration of tramadol provides better post-tonsillectomy pain control in the immediate postoperative period than bupivacaine or placebo without obvious side effects. Bupivacaine was superior to placebo in reducing early postoperative pain.